Terpene Profile, Leaf Anatomy, and Enzyme Activity of Resistant and Susceptible Cocoa Clonesto Vascular Streak Dieback Disease - Adi Prawoto; Teguh Iman Santoso; Marifah Marifah; Laurentius Hartanto Nugroho; Sutikno Slamet Sastroutomo (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2013)
Vascular-streak dieback (VSD, Oncobasidium theobromae) is the most prevalent disease of Theobroma cacao L. in Indonesia. This study aims to analyze resistance mechanism to VSD based on terpene profile, leaf anatomy, chitinase, and peroxidase study. Resistant clones of Sulawesi 1 and Sca 6 and susceptible clones of ICS 60 and TSH 858 were used for terpene profile, leaf anatomy analysis, chitinase, peroxides, polyphenol, lignin, and cellulose analysis. Those clones and KEE 2, KKM 22 and ICS 13 were used for peroxides analysis. For trichome study, the resistant clones of Sulawesi 1, Sca 6, KEE 2, and KKM 22, and susceptible clones of ICS 60 and TSH 858 were used. GCMS analysis showed that chromatogram pattern of resistant and susceptible groups were quite similar, but resistant clones contained 22% more components than the susceptible ones. Resistant clones contained groups of pinene, decane, myrcene, and octadecanoic acid, while those substances on usceptible clones were absent. Trichome was thicker on younger leaf, and its density on the basal was higher than that on the middle and tip leaf parts. Trichome density of resistant clone was not always thicker than that of susceptible ones. On resistant clones, stomatal density was lower and width of stomate pits was narrower, while thickness of epidermis layer and pallisade parenchym were higher. Polyphenol content of resistant clones were higher but lignin and cellulose of both groups were similar. Chitinase activity which has a role in hydrolysis of mycelia cell wall was higher on the resistant clones, but peroxides which has a role in polymeration of lignin biosynthesis was similar between both groups. It is concluded that groups of terpene pinene, decane, myrcene, and octadecanoic acid, thickness of leaf epidermis, density and width of stomata pit, and chitinase activity plays important role in cocoa resistance to VSD. Key words: Theobroma cacaoL., clone, vascular-streak dieback, resistance, leaf anatomy, chitinase, polyphenol